2015
DOI: 10.1111/edt.12238
|View full text |Cite
|
Sign up to set email alerts
|

Professional karate‐do and mixed martial arts fighters present with a high prevalence of temporomandibular disorders

Abstract: While there was a high prevalence of temporomandibular disorders in the professional athletes in our study, the prevalence of the condition in recreational athletes was similar to that in individuals who did not practice martial arts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 19 publications
(22 reference statements)
3
57
2
1
Order By: Relevance
“…Most were lacerations of the oral mucosa and skin abrasions, which are injuries for which the use of a mouthguard would not have had an effect. However, previous studies have demonstrated that amateur athletes are more prone to orofacial injuries than professional athletes 13,14 . Kreiswirth et al .…”
Section: Discussionmentioning
confidence: 91%
“…Most were lacerations of the oral mucosa and skin abrasions, which are injuries for which the use of a mouthguard would not have had an effect. However, previous studies have demonstrated that amateur athletes are more prone to orofacial injuries than professional athletes 13,14 . Kreiswirth et al .…”
Section: Discussionmentioning
confidence: 91%
“…4 In addition to concussions and traumatic brain injury, MMA athletes are also at risk for a number of facial and neck injuries. 8,37 Facial lacerations are common, particularly in the periorbital region, because of the prominence of facial bones and relative local hypervascularity. 3 These lacerations are especially troublesome during competitions, as bleeding leads to visual impairment and may even cause fight cancellation.…”
Section: Nonorthopaedic Injuries and Conditionsmentioning
confidence: 99%
“…A research that investigated the association between being a musician and having shoulder, neck and head pain, or having TMD symptoms, found results that support the association between the presence of TMD and the practice of woodwind instruments 16 . When comparing the prevalence obtained in this study with prevalence in other risk groups, such as high impact athletes, a study with professional of mixed martial arts showed that 61% of them had some type of TMD, while the prevalence among athletes of the Brazilian karate team was 54% 17 . One of the characteristics that these groups have in common is their frequent exposure to competition anxiety and stress.…”
Section: Discussionmentioning
confidence: 74%